Negative Histology after Endoscopic Resection: How to Avoid It - Yong Hwan Kwon (Yong Chan Lee, 2018)
Endoscopic resection (ER) is the current standard of care for selected cases of gastric epithelial dysplasia or early gastric cancer because of its curative en bloc resectability and complete histopathological assessment of the specimen. Although ER provides many advantages to surgery, some adverse events, such as bleeding, perforation, and local recurrence, can occur during and after the procedure. Furthermore, negative pathological findings after ER cause concerns about the adequacy of the procedure and local recurrence after ER among endoscopists and patients. Several variant factors, such as complete removal of small gastric tumor lesions by using initial forceps biopsy, pathological inconsistencies between pathologists, and performing ER in the wrong area. Thus, endoscopists must consider these risk factors to avoid and manage negative pathological results.